The Abstract Book of the XXII Conference of Junior Researchers in Psychology - Guogaitė, Greta; Grigaitė, Agnė; Rudytė, Miglė (Vilnius University Proceedings, 2025)
Conference of Junior Researchers in Psychology is an annual event organised by the doctoral students of the Institute of Psychology of Vilnius University. The conference provides an opportunity for psychology students and young researchers from Lithuanian and foreign universities to present their research and discoveries. This year's conference was dedicated to exploring the challenges and opportunities of everyday life in a changing world.
Keywords: Junior researchers; abstract book; psychology conference